War and the law of nations : a general history - Neff, Stephen C. (Cambridge University Press, 2005)
This volume is a history of war, from the standpoint of international law, from the beginning of history to the present day. Its primary focus is on legal conceptions of war as such, rather than on the substantive or technical aspects of the law of war.